Structural design and behavior of prestressed cable domes. (15th April 2020) - Krishnan, Sudarshan
Highlights: The paper provides insights about the structural behavior of cable domes. An equivalent planar model is derived for efficient analysis and strength design. Parametric effects on strength, stiffness and stability of domes are discussed. The paper discusses the design decisions for member and system stability. The governing limit states for a series of dome configurations are examined. Stayed-struts are recommended as design enhancement for higher buckling capacity. Abstract: A cable dome system is a spatial network of cables and struts that are pin-jointed, and whose forces are eventually brought to balance by a perimeter ring beam and supporting walls or columns. This paper provides insights about the structural design and behavior of prestressed radial-type cable domes. Through a study of parametric effects, the paper emphasizes careful selection of geometric parameters and cable prestressing forces. A simplified planar model equivalent to that of a three-dimensional model is derived for efficient analysis and design under symmetric loading conditions. The equivalent planar parameters are obtained using the geometrical and nodal force equilibrium relationships, and the Principle of Virtual Work. Results from planar analysis are compared and validated with the three-dimensional analysis results. The calculation of initial member sizes and initial cable prestressing forces is explained. This is followed by a discussion of the structural behavior of cable domes under asymmetric snow loads and wind uplift and the ensuing stability issues. The analysis results revealed that either strut buckling or overall system stiffness were the dominant limit states, the former being the governing limit state in domes with fewer hoops. A design enhancement in the form of cable-stayed struts is as such recommended to not only increase the strut buckling strength, but also to substantially increase a dome's load bearing capacity.